Sistem Keamanan Kotak Paket Cerdas Berbasis IoT dengan Teknologi MQTT - Sasmoko, Dani; Reni Veliyanti; S. Anang Wijayanto (LogicLink, 2024)
MQTT protocol is used by smart package box security systems based on the Internet of Things (IoT) to ensure the security and speed of package delivery. This system uses ESP32 devices and several sensors, including a keypad and magnetic sensors, as well as actuators like door lock solenoids and an LCD connected to an MQTT server that can be accessed via Android devices. The main features of this system include notifications about package arrivals, recipient identity verification using the last four digits of the phone number, and two operating modes, automatic and manual. After being tested under various conditions, this system has shown that it can effectively maintain security and monitor package status in real-time. The test results show that the smart package box hardware and the MQTT server can communicate well, allowing couriers and owners to communicate.